Intercomparison of the KOPRA and the RFM radiative transfer codes - Glatthor, N; Hopfner, M; Stiller, G; Von Clarmann, T; Dudhia, A; Echle, G; Funke, B; Hase, F (Society of Photo-Optical Instrumentation Engineers, 1999)
We discuss the intercomparison between the Karlsruhe Optimized and Precise Radiative transfer Algorithm (KOPRA) and the Reference Forward Model (RFM) codes, which have been designed for analysis of MIPAS-ENVISAT data. The purpose of this intercomparison is to validate the KOPRA algorithm, i.e. to identify and to remove possible errors in the KOPRA (or RFM) code and to quantify the reason of remaining differences. Similar comparisons between the MIPAS Optimised Forward Model (OFM) and the RFM as well as between KOPRA and the RFM have already been performed(Ref.(1,2)). To be able to relate on these results, this validation is similarly organised: we perform subsequently more complex tests of ray-tracing, integrated column amounts, homogeneous and limb path calculations of unapodised, apodised and held-of-view (FOV) convolved spectra, using the same isolated CO2 line as well as the same six MIPAS microwindows. Additionally we compare modelling of CO2 line-mixing non-local thermodynamic equilibrium (NLTE), trace gas continua and cross-section spectra.The KOPRA-RFM residuals are below a quarter of the noise-equivalent spectral radiance (NESR) for the isolated CO2 line as well as for the MIPAS microwindows, i.e. KOPRA fulfils the acceptance criteria requested for the OFM. In most cases the deviations are even clearly below 1 nW/(cm(2) sr cm(-1)), that is more than one order of magnitude below the acceptance threshold. This is valid for unconvolved as well as for ALS (apodised line shape) and FOV convolved spectra. There is also good agreement in modelling of the H2O-, O-2- and N-2-continua and of CO2 line-mixing. Larger deviations of up to several nW/(cm(2) sr cm(-1)) occured for NLTE calculations on the basis of "default" atmospheric profiles with vertical resolution of I or 2.5 km. These differences were found to be due to different layer-averaging of the vibrational temperatures and could be considerably reduced by calculations with a higher vertical resolution of 250 m. Cross-section spectra agree well, if the tabulated data are given independent of pressure, e.g. for ClONO2 and N2O5, and cover the atmospheric temperatures. Due to different temperature extrapolation the deviations increase up to 10 nW/(cm(2) sr cm(-1)) for atmospheric temperatures outside the measuring range. The RFM is not yet adjusted to cross-sections tabulated for non-equidistant temperatures and for atmospheric pressures, like CFC-data in the HITRAN96 database. If these data are used, larger differences arise, e.g, up to 30 nW/(cm(2) sr cm(-1)) between CFC-12 spectra. Avoidance of interpolation by performing homogeneous path calculations for p,T of one of the tabulated cross-section datasets reduces the deviations to below 0.5 nW/(cm(2) sr cm(-1)).